FACTORS OF INNOVATION AND COMPETITIVENESS OF BRAZILIAN BIO INDUSTRIES - de Morais, Cristiane Bonatto; Gelinski Junior, Eduardo; Scaratti, Dirceu; Bitencourt, Patricia Padilha (Anais eletrônicos do International Symposium on Science and Biotechnology, 2017)
Innovation is one of the priority elements for the competitive advantage of organizations. Bio-industries are part of a segment of companies that uses biotechnology to add value to their products and services. The identification of key factors of innovation contributes for companies of this niche area to make assertive decision making to enter and remain in an extremely competitive market of large companies and clusters. The methodology of the present study was based on bibliographical research of pertinent Brazilian legislation, the Oslo manual, CAPES database, journals and other publications in the area. In addition, it was considered fundamental elements of the MCTI, EMBRAPII and guidelines of FINEP, FNDCT and FAPESC to subsidize the definition of recent factors that authors cites and approach to define strategies of innovation and competitive positioning of bio-industries. The results contemplate a set of innovation and competitiveness factors within the scope of internal and external performance of this business segment, composed of intellectual capital, R & D & I (Research, Development & Infrastructure), regulatory environment, strategic alliances, costs, human capital, production and control systems, segregated in 53 sub-factors, which allows the identification and subsequent analysis aiming to contribute to the improvement of the respective bio-industries.